Preparation and characterization of superporous hydrogel based on different polymers - Chavda, Hitesh V; Patel, Rupal D; Modhia, Ishan P; Patel, Chhagan N (International Journal of Pharmaceutical Investigation)
Introduction: Superporous hydrogel (SPH) swells very rapidly in a shorter period of time to an equilibrium size and contains highly porous structure. Aim: The synthesis of SPH of poly (acrylamide-co-acrylic acid) and its composites viz. Ac-Di-Sol and polyvinylpyrollidone (PVP) was carried out by solution polymerization. Materials and Methods: The SPH and SPH composites (SPHCs) were characterized by measurement of apparent density, porosity, swelling, mechanical strength, and scanning electron microscopy (SEM) studies. Results: FTIR studies confirmed the existence of acrylamide and acrylic acid in SPH. In distilled water SPH showed tremendous increase in equilibrium swelling capacity with conventional SPH as compared to its SPHCs of Ac-Di-Sol and PVP due to the increased in physical cross-linking network, respectively. The presence of Ac-Di-Sol and PVP in SPHCs increased the mechanical strength as compared to conventional SPH which is suitable for gastric retention. SEM pictures clearly indicated the formation of interconnected pores and capillary channels. Conclusion: The amount and type of polymers used affect almost all the characterization parameters of SPHs, and hence, depending upon the applications perspective such polymers could be used in drug delivery systems, successfully.
Keywords: Ac-Di-Sol; mechanical strength; PVP; swelling